2021
DOI: 10.3389/fpubh.2021.724494
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Crisis Management: Lessons From the United Arab Emirates Leaders

Abstract: This study analyses the UAE leadership's approach in response to the COVID-19 crisis through the Organization for Economic Co-operation and Development's Strategic Crisis Management Framework. This framework analyzes the crisis management in three phases: the preparedness, the response to mitigate damage and the feedback mechanism after the crisis. The analysis showed that the key components of the UAE's crisis management included efficient and able governance, integrated utilization of public-private partners… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 3 publications
(4 reference statements)
0
14
0
Order By: Relevance
“…In summary, this study lays the foundation for future studies to bridge the gap between the polymorphisms and their possible involvement in the dysregulation of ACE2 in COVID-19. A limitation to our study includes the lack control samples (non-COVID-19) due to the difficulty in achieving patients’ samples that were not vaccinated, as vaccination process in the United Arab Emirates (UAE) has been initiated effectively by treated all people as emergency patients 36 , 37 . Moreover, additional information regarding demographic and pre-existing conditions such as smoking status for each patient were not provided.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, this study lays the foundation for future studies to bridge the gap between the polymorphisms and their possible involvement in the dysregulation of ACE2 in COVID-19. A limitation to our study includes the lack control samples (non-COVID-19) due to the difficulty in achieving patients’ samples that were not vaccinated, as vaccination process in the United Arab Emirates (UAE) has been initiated effectively by treated all people as emergency patients 36 , 37 . Moreover, additional information regarding demographic and pre-existing conditions such as smoking status for each patient were not provided.…”
Section: Discussionmentioning
confidence: 99%
“…While readmission rates for the reported HMP-O 2 are higher than overall readmissions for COVID-19 patients not involved in an HMP (here, 35% vs. 4–20%; Gavin et al, 2021 ), they are similar to the 25% readmission rate reported by Llorens et al for a home health program that directly discharged mild COVID-19 from the ED. Notably, that program reported a 77% cost-savings for these patients ( Abbas Zaher et al, 2021 ), but did not include patients requiring oxygen ( Llorens et al, 2021 ). Other hospitals developed a hybrid model, Atrium Health provided virtual monitoring for mild patients and in-person appointments for moderate to severe patients that would normally be in the hospital ( Sitammagari et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Future interventions focused on rest and social support for healthcare workers can be implemented as explained in the systemic review [27]. Abu Dhabi was rated among the best-performing cities in the world regarding the preparedness and supportive measures among them, including the healthcare system [29]. Nevertheless, the mental health of the healthcare workers seems an area worth investing in with the high depression and anxiety found.…”
Section: Plos Onementioning
confidence: 99%